Multi-objective optimization of flat-plate solar collectors using the Taguchi method and Grey relational analysis - Lohakare, Shraddha Sanjay; Rathod, Nikhil J. (Journal of Neonatal Surgery, 2024)
Flat-plate solar collectors are widely used in solar water heating systems, but their thermal performance depends strongly on design and processing parameters. This study presents a multi-objective optimization of a flat-plate solar collector using the Taguchi method combined with Grey relational analysis. Six control factors—collector tube material, absorber plate material, number of collector tubes, tube diameter, absorption film type, and insulation thickness—along with two noise factors were investigated using an L18 orthogonal array to minimize experimental effort. The efficiency coefficient and heat dissipation factor were selected as performance characteristics and evaluated using larger-the-better and smaller-the-better criteria, respectively. Signal-to-noise ratios and ANOVA were employed to assess robustness and parameter significance. Results show that the number of collector tubes is the most influential factor, followed by absorber plate material and absorption film type. The optimized parameter combination significantly improved collector performance, and confirmation experiments validated the proposed optimization model...